2010
DOI: 10.1128/jb.00028-10
|View full text |Cite
|
Sign up to set email alerts
|

Two Spx Proteins Modulate Stress Tolerance, Survival, and Virulence inStreptococcus mutans

Abstract: Previous work suggested that the underlying mechanisms by which the Streptococcus mutans ClpXP protease affects virulence traits are associated with accumulation of two orthologues of the Spx regulator, named SpxA and SpxB. Here, a thorough characterization of strains lacking the spx genes (⌬spxA, ⌬spxB, and ⌬spxA ⌬spxB) revealed that Spx, indeed, participates in the regulation of processes associated with S. mutans pathogenesis. The ⌬spxA strain displayed impaired ability to grow under acidic and oxidative st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
234
1
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 113 publications
(249 citation statements)
references
References 55 publications
12
234
1
2
Order By: Relevance
“…lactis encodes seven Spx paralogs, among which SpxB has been shown to be involved in the cell wall stress response. DNA microarray work with spx mutants confirmed the function of Spx as a major oxidative stress regulator (346,347). Streptococci harbor two bona fide Spx regulators, whereas enterococci have only one (346)(347)(348)(349).…”
Section: Treating Damaged Macromoleculesmentioning
confidence: 96%
See 1 more Smart Citation
“…lactis encodes seven Spx paralogs, among which SpxB has been shown to be involved in the cell wall stress response. DNA microarray work with spx mutants confirmed the function of Spx as a major oxidative stress regulator (346,347). Streptococci harbor two bona fide Spx regulators, whereas enterococci have only one (346)(347)(348)(349).…”
Section: Treating Damaged Macromoleculesmentioning
confidence: 96%
“…Recent studies have shown that streptococcal genomes encode two copies of the redox-sensing Spx regulator, designated SpxA1 and SpxA2. In S. mutans, loss of spxA1, spxA2, or both attenuated virulence in the G. mellonella invertebrate model (346), while the ability to colonize the teeth of rats was significantly impaired in the ⌬spxA1 mutant and the double mutant but not in the ⌬spxA2 mutant (346). SpxA1 and SpxA2 were shown to modulate stress tolerance in S. suis, and loss of spxA1 or spxA2 significantly reduced the ability of S. suis to survive in pig blood and to disseminate to different tissues (347).…”
Section: Oxidative Stress and Virulencementioning
confidence: 99%
“…In Streptococcus mutans, the causative agent of tooth decay, mutations in virulence or global regulatory genes (including genes involved in stress responses) strongly affect gene transcription (81)(82)(83)(84)(85), including that of the type II cas genes ( Fig. 1 and 4).…”
Section: Transcriptome Analysis Of the Cas Genesmentioning
confidence: 99%
“…In fact, it was the pioneering work conducted in the 1950s and 60s using hamsters and gnotobiotic rats that established S. mutans as the principal aetiological agent of dental caries (Fitzgerald & Keyes, 1960;Orland et al, 1955;Zinner et al, 1965). More recently, several studies have demonstrated the usefulness of the infection of the larvae of Galleria mellonella to study the pathogenic potential of S. mutans strains in systemic infections (Abranches et al, 2011;Gonzalez et al, 2012;Kajfasz et al, 2010). Despite its obvious limitations, this increasingly popular model may be viewed as a powerful and inexpensive screening tool for studying bacterial fitness and virulence, in particular for traits that are associated with resistance to hostderived stress factors during systemic diseases.…”
Section: S Mutans As a Model Organism Of Pathogenic Gram-positive Bamentioning
confidence: 99%